THE INFLUENCE OF SCHOOL LITERACY ENVIRONMENT MANAGEMENT ON STUDENTS’ READING INTEREST AND SELF-EFFICACY IN ISLAMIC EDUCATION IN INDONESIA - Syahrida; Jasiah (World Psychology, 2026)
Literacy development has become a central concern in Islamic education in Indonesia, particularly in relation to students’ reading interest and self-efficacy as key foundations for academic engagement and lifelong learning. School literacy environment management is assumed to play a strategic role in shaping these outcomes, yet its influence has not been sufficiently examined within Islamic educational contexts. This study aims to analyze the influence of school literacy environment management on students’ reading interest and self-efficacy in Islamic education in Indonesia. The study employed a qualitative research design using a descriptive–analytical library research approach, drawing on peer-reviewed journal articles, academic books, policy documents, and research reports relevant to literacy management and Islamic education. Data were analyzed through thematic synthesis to identify patterns and relationships among literacy environment management, reading interest, and self-efficacy. The findings indicate that well-managed literacy environments characterized by systematic planning, availability of reading facilities, teacher facilitation, and integration of Islamic values significantly enhance students’ motivation to read and strengthen their confidence in reading abilities. Reading interest and self-efficacy were found to be interrelated outcomes shaped by institutional literacy practices rather than individual factors alone. The study concludes that effective school literacy environment management provides a sustainable pathway for fostering motivated and confident readers in Islamic education, highlighting the importance of managerial and cultural dimensions in literacy development.